2020
DOI: 10.1088/1748-9326/abaa7a
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on the spatial, temporal, and vertical distribution of biomass burning: quantifying a significant increase in CO emissions

Abstract: A variance-maximization approach based on 19 years of weekly measurements of pollution in the troposphere carbon monoxide (CO) measurements quantifies the spatial-temporal distribution of global biomass burning. Seven regions consistent with existing datasets are discovered and shown to burn for longer, over a more widespread area. Each region has a unique and recurring burning season, with three dominated by inter- and intra-annual variation. The CO is primarily lofted to the free troposphere from where it sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…5 are found to generally be consistent, with the ratio found to be more so (Table S2). This indicates the NO 2 /CO column ratio over the fire regions tends to be consistent with the fire plumes as a whole and is not found to be significantly influenced by urban sources of NO 2 , which would lead to a vastly faster chemical titration of NO 2 compared to CO. All of these results are also shown to be consistent with recent work (Cohen, 2014;Lin et al, 2014Lin et al, , 2020a, showing that the characteristics of the spatial-temporal variability of fires are quite different from those of urban areas and have a much higher variability both week to week and interannually.…”
Section: Regression Model Applied To Misr Omi Mopitt and Meteorologsupporting
confidence: 91%
See 1 more Smart Citation
“…5 are found to generally be consistent, with the ratio found to be more so (Table S2). This indicates the NO 2 /CO column ratio over the fire regions tends to be consistent with the fire plumes as a whole and is not found to be significantly influenced by urban sources of NO 2 , which would lead to a vastly faster chemical titration of NO 2 compared to CO. All of these results are also shown to be consistent with recent work (Cohen, 2014;Lin et al, 2014Lin et al, , 2020a, showing that the characteristics of the spatial-temporal variability of fires are quite different from those of urban areas and have a much higher variability both week to week and interannually.…”
Section: Regression Model Applied To Misr Omi Mopitt and Meteorologsupporting
confidence: 91%
“…One advantage of the OMI NO 2 column measurements is that they can often be observed under relatively cloudy or smoky conditions (Lin et al, 2014). Another advantage is that the atmospheric lifetime of NO 2 is only a few hours, and therefore relatively large changes in the temporal-spatial distribution of NO 2 column measurements are highly correlated with wildfire sources (Lin et al, 2020a;He et al, 2020).…”
Section: Omi Nitrogen Dioxide (No 2 ) Measurementsmentioning
confidence: 99%
“…The spatial distribution shows the highest levels of BC over the biomass burning source regions in the north, with a smaller but still significant burden over emissions regions in the south. Second, there is a significant amount of eastward transport observed at all size ranges of BC, with the smaller sizes (BC1 and BC2) having a significant amount of transport two‐thirds of the way across the South China Sea (to about Dongsha Island) and the larger size ranges (BC3–BC6) exhibiting eastward transport all the way to Taiwan or beyond into the Pacific Ocean, consistent with the flow induced by the Indian Ocean monsoon on observations of CO (C. Lin, Cohen, Wang, Lan, et al., 2020). Third the geographic spread of BC4 has the largest total area, reaching as far east as the Western Pacific Ocean, as far South as 7°N, as far southeast as the Philippines, and as far southwest as the Indian Ocean.…”
Section: Resultssupporting
confidence: 68%
“…Some work has been able to obtain a good match with respect to ground-based observation of PM2.5 (Le et al, 2020;Zhang et al, 2019), PM10 Wang, 2013), carbon monoxide (CO) (Reid et al, 2013;Reid et al, 2005) , and ozone (Ding et al, 2013), within the respective sub-regions. However, to date, there has been no modeling study able to match the large-scale and coherent plumes in terms of space, time, duration, height, and magnitude over this region of the world, as identified by remotely sensed measurements of AOD from MISR (Cohen, 2014), combination of AOD, fire hotspots, and land-surface change from MODIS (Cohen et al, 2017), a combination of AOD from MISR and Height from CALIOP (Cohen et al, 2018), CO from MOPITT (Lin et al, 2020a;Lin et al, 2020b), and a combination of NO2 from OMI, CO from MOPITT, and height from MISR (Wang et al, 2020).Furthermore, there is no modeling study found able to show a significant amount of transport from Continental Southeast Asia to the Maritime Continent (Reid et al, 2013). Yet, due to the complexity of the geography, meteorology, and dynamics, as well as intense cloud-cover in Southeast Asia, models provide an important component for improving the understanding of the sources and transport of aerosols over this region of the world (Lin et al, 2013;Reid et al, 2012).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation